The image of the cat in Portuguese and Romanian proverbs - Ciama, Adriana (Romanica Olomucensia, 2024)
The aim of this study is to present a comparative analysis of proverbs with the word cat in Portuguese and Romanian. Proverbs are part of the cultural memory of a community and they can be considered privileged elements that allow us to more easily observe the interaction between language and culture. This comparative analysis of proverbs focuses on two levels, lexical and semantic. At the lexical level the lexemes that make up the structure of proverbs are analysed. They are grouped into various archilexemes (animals, domestic space, food, natural phenomena, etc.). The comparison between the two languages highlights not only similarities, but also differences (lexical richness, toponyms, cultural references in Portuguese). The semantic analysis allows two aspects to be explored. First, the most prominent characteristics of cats that are reflected in proverbs are examined, with the conclusion that, despite some similarities, the images of the cat do not always coincide in the two languages; thus, in Portuguese the image of a mewing cat stands out, while in Romanian it is the image of an old cat. Second, since animals are commonly used as terms of comparison in order to highlight not only human beings' good qualities but also their flaws, in the last part of the article some similar thematic areas in both languages are identified (hypocrisy, appearances, and lack of authority, among others), but also others that are specific to each language (ingratitude and vanity in Portuguese, poverty and greed in Romanian). The analysis is based on a representative corpus made up of 98 proverbs in Portuguese and 72 in Romanian, collected from the main dictionaries of proverbs in both languages.
Keywords: proverbs; Portuguese; Romanian; cat; comparative analysis